Strategies for Controlling Gambling Practices in Military Personnel Settings - Triawan, Rio; Khaerudin, Khaerudin (Dinasti International Journal of Management Science, 2025)
Gambling practices are vulnerable among the military. There are many risk factors for gambling addiction, including work stress, being away from family and loneliness, low levels of screening from the start of admission, screening during work, and post-placement. This review aims to identify strategies for managing the impact of gambling addiction on personnel in the military environment. A literature review design was used in this study using the ScienceDirect, PsycInfo, and Google Scholar data bases. The articles reviewed are articles published for the 2020-2024 period. There were 5 articles that met the inclusion criteria and were reviewed. The results of this review show that there is no specific strategy for managing gambling addiction in the military environment, but it needs to be designed to control the negative effects of gambling addiction in the military environment